Transient regional osteoporosis - F. Trotta; N. Prandini; C. Orzincolo; A. Massara (PAGEPress Publications, 2011)
Transient osteoporosis of the hip and regional migratory osteoporosis are uncommon and probably underdiagnosed bone diseases characterized by pain and functional limitation mainly affecting weight-bearing joints of the lower limbs. These conditions are usually self-limiting and symptoms tend to abate within a few months without sequelae. Routine laboratory investigations are unremarkable. Middle aged men and women during the last months of pregnancy or in the immediate post-partum period are principally affected. Osteopenia with preservation of articular space and transitory edema of the bone marrow provided by magnetic resonance imaging are common to these two conditions, so they are also known by the term regional transitory osteoporosis. The appearance of bone marrow edema is not specific to regional transitory osteoporosis but can be observed in several diseases, i.e. trauma, reflex sympathetic dystrophy, avascular osteonecrosis, infections, tumors from which it must be differentiated. The etiology of this condition is unknown. Pathogenesis is still debated in particular the relationship with reflex sympathetic dystrophy, with which regional transitory osteoporosis is often identified. The purpose of the present review is to remark on the relationship between transient osteoporosis of the hip and regional migratory osteoporosis with particular attention to the bone marrow edema pattern and relative differential diagnosis.